Coincidence-anticipation timing and reaction time in youth tennis and table tennis players - Ak, E.; Kocak, S. (Perceptual and Motor Skills, 2010)
The purpose of this study was to compare the coincidence-anticipation timing and reaction times (RT) of 10- to 14-year-old tennis and table tennis players and examine possible sex differences. 107 (51.4%) tennis and 101 (48.6%) table tennis players participated in this study. Players were compared on coincidence-anticipation timing and reaction time. Tennis players performed with less error in the coincidence-anticipation timing task than table tennis players, whereas table tennis players had lower mean reaction time than tennis players. It was also found that male players made fewer errors in the coincidence-anticipation timing task than their female counterparts.